WEBSITE-BASED INVENTORY INFORMATION SYSTEM AT WAHANA SERVICE - Yonatan Yonatan; Devi Yurisca Bernanda (Jurnal Teknoinfo, 2023)
The rapid development of Information Technology at this time has changed human activities and mobility. These changes occur in various areas of human life, including in the world of industry and business. Many companies are starting to compete to take advantage of this Information Technology development to provide convenience and increase their competitive advantage in order to increase competitiveness. This phenomenon has also begun to affect the Wahana Service workshop business processes. Wahana Service Workshop at this time still does not utilize Information Technology in its business processes, especially in the process of recording stock, incoming goods and outgoing goods. The process of recording and processing the data is still done manually so it is quite time consuming and prone to errors. The process of making reports is also still done manually so it is quite time consuming and prone to errors. To solve this problem, this research was made. The end result of this research is the Wahana Service inventory information system. Inventory is a process related to recording data on goods and assets owned by the company. Inventory itself is an important thing in a sales company like Wahana Service. Therefore the designed Wahana Service inventory system will play an important role in the company's business processes. Wahana Service's inventory information system will be designed based on a website to increase flexibility and responsiveness. The process of making the system will use the Waterfall method as the system development method. Waterfall itself is the most commonly used system development method in making systems. It is hoped that by using the waterfall, the designed system will have good quality and minimal errors. In designing the Wahana Service inventory information system, it adopts a structured programming paradigm and is written using the HTML, CSS, PHP, Javascript and MySQL database programming languages. The author also uses the Boostrap5 framework to produce an attractive and responsive website appearance. It is hoped that with the website-based Wahana Service inventory information system, the process of recording and reporting stock, incoming and outgoing goods can be done more quickly and safely. In addition, the use of this system will also be easier because it is compatible with any device and the data displayed is realtime.